PENDAMPINGAN PETANI MUDA KOPI ROBUSTA DALAM UPAYA MENINGKATKAN EKSISTENSI PETANI KOPI DI DESA AMADANOM, KECAMATAN DAMPIT, KABUPATEN MALANG - Zahidi, M. Syaprin; Prakoso, Havidz Ageng; Agustino, Hutri; Septia, Erfan Dani (UNIVERSITAS PGRI MADIUN, 2020)
Abstract. Amadanom Village, Dampit District, Malang Regency is known as Robusta coffee granary but at present there are problems faced by coffee farmers in Amadanom Village. The problem is about the regeneration of coffee farmers who are hampered by the lack of interest in the young generation in Amadanom Village to continue their parents' profession as coffee farmers. So, in this service program we focus the program on coffee literacy classes which are held intensively for 30 days. The purpose of this activity is to encourage young people in Amadanom Village to continue their parents' work as coffee farmers. The method of activities that we do is to hold workshops that bring experts in the fields of Branding, Information Technology, Agrotechnology and Online Marketing. This community service has succeeded in forming a Young Farmers Group who is committed to continuing the profession of their parents as coffee farmers in Amadanom Village.Abstrak. Desa Amadanom, Kecamatan Dampit, Kabupaten Malang dikenal sebagai lumbung kopi robusta namun pada saat ini ada permasalahan yang dihadapi oleh para petani kopi di Desa Amadanom. Masalah itu adalah tentang regenerasi petani kopi yang terhambat akibat dari kurang berminatnya generasi muda di Desa Amadanom untuk melanjutkan profesi orang tuanya sebagai petani kopi. Maka, dalam program pengabdian ini kami memfokuskan program pada kelas literasi kopi yang diadakan secara intensif selama 30 hari. Tujuan dari kegiatan ini adalah mendorong generasi muda di Desa Amadanom untuk melanjutkan pekerjaan orang tuanya menjadi petani kopi. Adapun metode kegiatan yang kami lakukan adalah dengan mengadakan workshop yang mendatangkan para ahli di bidang Branding, Teknologi Informasi, Agroteknologi dan Marketing Online. Kegiatan pengabdian ini berhasil membentuk Kelompok Petani Muda yang berkomitmen untuk meneruskan Profesi orang tuanya sebagai petani kopi di Desa Amadanom.